Injectable thermo-sensitive hydrogel loaded hollow copper sulfide nanoparticles for ROS burst in TME and effective tumor treatment - Ning, Shipeng; Mo, Jianlan; Huang, Rong; Liu, Benkun; Fu, Bicheng; Ding, Shuaijie; Yang, Huawei; Cui, Ying; Yao, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Lung cancer the most prevalent cause of cancer-related deaths, and current therapies lack sufficient specificity and efficacy. This study developed an injectable thermosensitive hydrogel harboring hollow copper sulfide nanoparticles and β-lapachone (Lap) (CLH) for lung tumor treatment. Methods: The hydrogel-encapsulated CLH system can remotely control the release of copper ions (Cu2+) and drugs using photothermal effects for non-invasive controlled-release drug delivery in tumor therapy. The released Cu2+ consumes the overexpressed GSH in TME and the generated Cu+ further exploits the TME characteristics to initiate nanocatalytic reactions for generating highly toxic hydroxyl radicals. In addition, in cancer cells overexpressing Nicotinamide adenine dinucleotide (phosphate): quinone oxidoreductase 1 (NQO1), Lap can catalyze the generation of hydrogen peroxide (H2O2) through futile redox cycles. H2O2 is further converted into highly toxic hydroxyl radicals via the Fenton-like reaction, leading to a burst of reactive oxygen species in TME, which further enhances the therapeutic effect of chemokines. Results: Analysis of the antitumor efficacy in a subcutaneous A549 lung tumor model mice showed a significant delay in tumor growth and no systemic toxicity was detected. Discussion: In conclusion, we have established a CLH nanodrug platform that enables efficient lung tumor therapy through combined photothermal/chemodynamic therapy (CDT) treatment and self-supplying H2O2 to achieve cascade catalysis, leading to explosive amplification of oxidative stress.